2005
DOI: 10.1093/cercor/bhi031
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evoked Potential Patterns to Voiced and Voiceless Speech Sounds in Adult Developmental Dyslexics with Persistent Deficits

Abstract: Auditory evoked potentials (AEPs) were recorded from eight developmental dyslexic adults with persistent reading, spelling and phonological deficits, and 10 non-dyslexic controls to voiced (/ba/) and voiceless (/pa/) consonant-vowel syllables. Consistent with previous data, non-dyslexics coded these stimuli differentially according to the temporal cues that form the basis of the voiced/voiceless contrast: AEPs had time-locked components with latencies that were determined by the temporal structure of the stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 74 publications
2
23
0
2
Order By: Relevance
“…In attentive processing, we demonstrated in a previous study a clear asymmetrical response pattern favouring the left posterior supratemporal plane during the attentional processing of temporal features in speech and non-speech sounds (Zaehle et al 2007a). Similarly, EEG and MEG studies (Giraud et al 2005;Sieroka et al 2003), and intracerebral recordings (Liegeois-Chauvel et al 1999) demonstrated an enhanced performance of the left compared to the right auditory cortex during the processing of temporal acoustic information.…”
Section: Discussionsupporting
confidence: 60%
“…In attentive processing, we demonstrated in a previous study a clear asymmetrical response pattern favouring the left posterior supratemporal plane during the attentional processing of temporal features in speech and non-speech sounds (Zaehle et al 2007a). Similarly, EEG and MEG studies (Giraud et al 2005;Sieroka et al 2003), and intracerebral recordings (Liegeois-Chauvel et al 1999) demonstrated an enhanced performance of the left compared to the right auditory cortex during the processing of temporal acoustic information.…”
Section: Discussionsupporting
confidence: 60%
“…We assume that the measured response reflects the sum of neural activity from the cortex rather than the auditory brainstem, given the low modulation frequency selected. Further, we have suggested that the cortical response for the AM-BBN alone is elicited by the onset of the stimulus [67][68][69] but that the response elicited by the AM-BBN following the BBN is elicited by the temporal change in the stimulus and represents an acoustic change complex (ACC). Consistent with this interpretation is that the cortical responses (and N2 latencies) are similar when elicited by the AM-BBN stimulus alone in the two extreme modulation conditions (100% compared with 0%).…”
Section: Discussionmentioning
confidence: 99%
“…It is perhaps the most common and most carefully studied neurobehavioral disorder affecting children, with reported prevalence rates ranging from 5% to 17% (Shaywitz et al, 1990;Lyon, 1995;Shaywitz, 1998;Giraud et al, 2005). Moreover, it is a neurobiological condition that reportedly affects approximately 80% of all individuals identifi ed as learning disabled (Bell et al, 2003;Shaywitz et al, 2007).…”
mentioning
confidence: 99%